Bioactive edible films for food applications: mechanisms of antimicrobial and antioxidant activity. Issue 21 (30th November 2019) - Benbettaïeb, Nasreddine; Debeaufort, Frédéric; Karbowiak, Thomas
Abstract: In order to improve the quality of food and to extend their shelf life, a new generation of active edible films is being especially intended after the incorporation of organic acids, enzymes, antimicrobial proteins, phenolic compounds, or other functional ingredients such as probiotics, flavors, vitamins and nutraceuticals. These active compounds have different mechanisms of action related to their structure, their concentration, the nature of micro-organism targeted, the process of encapsulation or incorporation in the biopolymer film-networks. The application of the active films by direct contact or indirect contact via the head space also affects the bioactivity of these compounds. This article critically reviews the published work on active edible-films and their applications for food preservation. The classes of active compounds and their action mechanisms are firstly discussed. Then, an extended overview on their effect on model food (simulants) or on real food during storage was also addressed. Edible films offer two main advantages over the direct incorporation of the antimicrobial or antioxidant agents into the bulk food: 1) to control the diffusion of active compounds at the surface of the food and 2) to reduce the amount of preservatives added in the food.